Avaliação do programa de mediação de conflitos familiares de uma instituição de ensino superior - Alcure, Felipe Augusto da Silva (2016)
Mediation is a form of conflict resolution whose origins go back over 2500 years in the past. This alternative method consists in a third party aiding on the development of communication among conflicting parties. This research consisted of an exploratory study regarding the activities performed in a Program of Family Conflicts Mediation developed by the Nucleus of Alternative Forms of Conflict Resolution of a Higher Education Institution. The following work had as objectives: providing information related to the view of those under the jurisdiction about the offered service, and the development of the mediations, which took place in Santa Felicidade’s court. In order to do that, a questionnaire with seven questions was applied after the ending of the last session performed on each conflict-solving process, as well as a semi-structured interview applied in a period no less than three months after the signature of the contract. As regards the evaluation of the service provided, out of sixteen people assisted, only one rated the service as “very bad”, two rated it “reasonable” and all the others rated it as “very good”. As for the satisfaction of the users with the resolution achieved, one answered that the mediation “in no way” offered a satisfactory resolution for the conflict; the same number of people answered “no”, “possibly not” and “maybe” for this question; two people responded that the mediation “possibly” provided a satisfactory outcome – same amount that answered “yes”, while the other eight replied that “definitely” the resolution achieved for the conflict was satisfactory). Concerning the usefulness of the information provided by the mediator in an eventual dispute in the future, one of the participants replied that “in no way” was it useful, the same number was observed with the answer “possibly yes”, while three people answered “yes” and the other 11 replied “definitely”. With regards to the possibility of presenting a new conflict for the appraisal of this Nucleus of Mediation, two people answered “no way”, while one participant commented that “possibly yes”; the other 13 stated that they would “definitely” do it. As for the evolution of the social relationship, nine of the interviewed understood that the relationship remained satisfactory whereas seven replied that it did not. The analysis of the procedure adopted in session and the perception of the users showed that those under jurisdiction did not establish a connection between the identification of the stages of the sessions and the success of the procedure, a datum which is in agreement with the transformative mediation modern theory. On the agreement fulfillment question, two interviewed answered that the agreement has not been completely fulfilled, four replied that the agreement has been partly fulfilled and ten stated that the agreement stablished on the mediation sessions has been wholly fulfilled. The existing challenge, regarding the appraisal from the user of the activity of the Nucleus of Mediation, was overcome with the feedback of fundamental information to the evolution of the implemented method on the family conflict sessions.